DOES THE CHOICE OF LANGUAGE IN TESTS HAVE AN IMPACT ON GENDER EQUALITY IN PRIMARY EDUCATION? A CASE STUDY IN SENEGAL - Chazeaud , Alexandre (African Journal of Education and Practice, 2021)
Purpose: The present study analyses the possible impact on gender equality when using a language familiar to students in tests at primary schools in Sub-Saharan Africa where a European language is the unique medium of instruction and assessment. Methodology: To this aim, students at grades 3 and 6 (83 girls and 66 boys) in primary schools in rural Senegal were given two different tests: Mathematics problem-solving tasks and multiple-choice questions of Social Sciences. They were divided at random into a control group if they received the tests in Seerer, the local language familiar to them, or French, the sole official language in the Senegalese education system. After data collection, results were codified for analysis considering two variables: Gender and grade. First, we calculated both the percentage of students who scored the set mark and those who obtained the highest scores. Second, we checked for statistically significant differences between groups by means of One-Way-ANOVA and Tukey tests. Findings: Although Seerer as language of tests was found to benefit both genders, results suggest that its use may especially determine girls' success at school: Girls in the experimental group obtained higher results than girls in the control group, especially the youngest, and many reached the highest scores. Unique contribution to theory, practice and policy: Findings suggest that first, the use of a language familiar to students in tests seems to have positive effects on their academic results, and second, that it may play a role in bridging the gap between genders in some education models thanks to the evident benefits for girls, especially young ones. Such results might be taken into consideration by education authorities together with other existing examples to introduce local languages in the education system of Senegal and other Sub-Saharan countries where only a European language is employed, as it seems to contribute to reaching gender equality in education. We suggest that local languages could be used in tests from the lower levels of primary education in bilingual programs, thus favouring transfer of linguistic skills and content from the local to the European language, and increasing school success